Pemahaman Huruf Hijaiyah dengan Menggunakan Media Kartu - Marlini Bante; Sukman Sukman; St Umrah (Al-Fikr: Jurnal Pendidikan Islam, 2018)
Students' understanding of hijaiyah material is the background of this research. This is based on observations and interviews conducted with teachers at the school. This study aims to improve student learning outcomes in hijaiyah letters using hijaiyah letter cards in class III students of SD Inpres 1, Sorong Regency. This research is a classroom action research (PTK) with the subjects of third-grade students of SD Inpres 1 Sorong Regency who is Muslim in the even semester of the academic year 2017/2018, amounting to 22 students. This research was conducted in 2 cycles using the Kemmis and Mc Taggart models with 4 stages of continuous repetitive research. Retrieval of data taken using teacher teaching observation sheets, student activity sheets, student learning outcomes data. The results obtained after the action are the percentage of completeness of the value from the pre-cycle, cycle I, and cycle II respectively are 27%, 68%, and 86%. From the results of this study, in general, it can be concluded that an increase in student learning outcomes in Islamic Religious Education (PAI) subjects in grade III students of SD Inpres 1 Sorong Regency after the implementation of learning using the hijaiyah letter card media.